Deletion of ddx4 Ovary-Specific Transcript Causes Dysfunction of Meiosis and Derepress of DNA Transposons in Zebrafish Ovaries - Yuanyuan Chen; Xing Lin; Jing Dai; Yifan Bai; Fei Liu; Daji Luo (Biology)
Alternative splicing of ddx4 (DEAD-box helicase 4), a key germline marker gene, has been reported to generate sex-specific transcripts in zebrafish gonads. The biological functions and regulatory mechanisms of the ddx4 ovary-specific transcript (ddx4-L) during oogenesis remain unclear. In this study, we found that ddx4-L mutants, in which ddx4-L was specifically deleted, had enlarged ovaries but laid fewer eggs, along with having a lower fertilization rate compared to WT controls. RNA-seq analysis was performed to detect the changes in gene expression between WT and ddx4-L mutant ovaries. A total of 524 upregulated and 610 downregulated DEGs were identified. GO and GSEA enrichment analyses showed that genes involved in fertilization and reproduction biological processes were significantly downregulated. More specifically, we observed a remarkable reduction in Sycp1, a core component of synaptonemal complex, in ddx4-L mutant ovaries at both the mRNA and protein levels. In addition, the expressions of transposon elements, as well as the events of alternative splicing, alternative polyadenylation, and RNA editing, were analyzed based on the RNA-seq data. We found that the deletion of ddx4-L resulted in derepression of DNA transposons in zebrafish ovaries, possibly causing genome instability. In conclusion, our work demonstrates that the ovary-specific ddx4 transcript plays important roles in oocyte meiosis and DNA transposon repression, which extends our understanding of the biological functions and regulatory mechanisms of sex-specific alternative splicing in zebrafish oogenesis and reproduction.